Kingdoms or Dynasties? Arabs, History, and Identity before Islam1 - Fisher, Greg (Journal of late antiquity, 2011)
This study examines the evidence for three small but prominent groups of Arabs in the fifth and sixth centuries-the Jafnids, allied to the Roman Empire, the Nasrids, allied to the Sasanians, and the Hujrids, client rulers of the kingdom of Himyar, but equally subject to pressure from the Romans and Sasanians. It explores the numerous problems that have impeded efforts to produce a balanced assessment of these peoples, including source-critical, historiographical, and ideological pressures. It also highlights the longheld attachment of each group to a "people," the Jafnids to Ghassan, the Nasrids to Lakhm, and the Hujrids to Kinda, connections that have produced a misleading impression of kingdoms or stable polities under each name. The evidence only allows us to describe family dynasties composed of small groups of individuals. Finally, highlighting the importance of the framework of imperial power in any analysis of the late antique east, it offers some thoughts on what the evidence discussed here suggests for our understanding of Arab identities before Islam. [PUBLICATION ABSTRACT]